Magical thinking and moral injury: exclusion culture in psychiatry. (February 2022) - Beale, Chloe
Abstract : Summary: This is an article about exclusion. We might not like to admit it – even fail to realise it – but National Health Service (NHS) mental health service structures have become increasingly focused on how to deny people care instead of help them to access it. Clinicians learn the art of self-delusion, convincing ourselves we are not letting patients down but, instead, doing the clinically appropriate thing. Well-meant initiatives become misappropriated to justify neglect. Are we trying to protect ourselves against the knowledge that we're failing our patients, or is collusion simply the easiest option? Problematic language endemic in psychiatry reveals a deeper issue: a culture of fear and falsehood, leading to iatrogenic harm. An excessively risk-averse and under-resourced system may drain its clinicians of compassion, losing sight of the human being behind each 'protected' bed and rejected referral.